EVALUASI SISTEM INFORMASI MANAJEMEN LOGISTIK MEDIS DENGAN METODE HOT FIT DI RUMAH SAKIT UMUM PERMATA BUNDA KOTA TASIKMALAYA - Tony Prabowo; Fadil Ahmad Junaedi; Depi Yulyanti; Nasywa Zulfa Nujmatul Arifin; Fitrhi Octavia (LPPM Universitas Awal Bros, 2026)
Medical logistics management information systems play a crucial role in ensuring the availability and distribution of medicines and medical equipment in hospitals. However, its effectiveness needs comprehensive evaluation. This study aimed to evaluate the Medical Logistics Management Information System (SIMLM) at Permata Bunda General Hospital, Tasikmalaya City, using the HOT Fit (Human, Organization, and Technology Fit) method. This study employed an evaluative design with a mixed methods approach (quantitative and qualitative). Data were collected through questionnaires distributed to 7 respondents and in-depth interviews with key informants from various units including pharmacy, outpatient, inpatient, emergency, IT, and hospital management during January to March 2025. Results showed that the Human aspect received good ratings, with 75% of users reporting comfort and 87.5% feeling capable of operating the system; 100% agreed that SIMLM improves work efficiency. The Organization aspect demonstrated adequate support, particularly in technical team availability (87.5%) and management transparency (87.5%), though gaps remain between policy and practice. The Technology aspect showed strengths in access speed (87.5%) but revealed weaknesses in system stability, as only 50% reported rare system errors, and 37.5% questioned data accuracy. In conclusion, SIMLM with the Khanza application has effectively supported hospital digitalization, yet improvements are needed in user training, management support operationalization, system stability, and data accuracy.